Passageiros do tempo e a experiência fotográfica: da modernidade analógica à contemporaneidade digital - Sanz, Cláudia Guilmar Linhares (2006)
This work aims to deal with the relation between temporal experience and photographic act. Nowadays, the world s macroeconomic reorganization and the monopoly of the communication media, both of them unleashed by the radical growth in the technology of velocity, definitely modify our subjective, individual and general experience, specially the conceptions about time and space. Nevertheless, in order to think about the mutations in which the contemporary subjectivity has gone through, specially the temporality experience, this text does a historical retrocession while investigating the temporal construction of the Modernity. In fact, there can be identified a modern temporal acceleration which is deeply linked with control and power discipline techniques, the space conquest and with the crisis of the representation. Today this acceleration amounts to exponential levels bringing to the economic and cultural activities gravity core the time control. Consequently the temporal itself alters: the contemporary man holds himself on to the past with no ambition of surpassing it, on the other hand, he does not see the future as an unknown horizon. It seems to mean that, at least as a tendency, the foundations of a progressive time which until then marked our cultural and moral visions, and also our way of photographing, are in transition.